Micro-computed tomographic evaluation of the flow and filling ability of endodontic materials using different test models - Fernanda Ferrari Esteves Torres; Juliane Maria Guerreiro-Tanomaru; Gisselle Moraima Chavez-Andrade; Jader Camilo Pinto; Fábio Luiz Camargo Villela Berbert; Mario Tanomaru-Filho (Restorative Dentistry & Endodontics)
ObjectivesThis study compared the flow and filling of several retrograde filling materials using new different test models.Materials and MethodsGlass plates were manufactured with a central cavity and 4 grooves in the horizontal and vertical directions. Grooves with the dimensions used in the previous study (1 × 1 × 2 mm; length, width, and height respectively) were compared with grooves measuring 1 × 1 × 1 and 1 × 2 × 1 mm. Biodentine, intermediate restorative material (IRM), and mineral trioxide aggregate (MTA) were evaluated. Each material was placed in the central cavity, and then another glass plate and a metal weight were placed over the cement. The glass plate/material set was scanned using micro-computed tomography. Flow was calculated by linear measurements in the grooves. Central filling was calculated in the central cavity (mm3) and lateral filling was measured up to 2 mm from the central cavity.ResultsBiodentine presented the least flow and better filling than IRM when evaluated in the 1 × 1 × 2 model. In a comparison of the test models, MTA had the most flow in the 1 × 1 × 2 model. All materials had lower lateral filling when the 1 × 1 × 2 model was used.ConclusionsFlow and filling were affected by the size of the test models. Higher grooves and materials with greater flow resulted in lower filling capacity. The test model measuring 1 × 1 × 2 mm showed a better ability to differentiate among the materials.